Cognitive and Neuropsychiatric Manifestations of COVID-19 in elderly people with and without dementia: A literature review - Bombón-Albán, Paulina E. (2022)
During the severe acute respiratory syndrome due to the COVID-19 pandemic, dementia has been identified as disproportionately common in elderly people than 65 years who develop a serious viral infection. Data from the International Consortium on Severe and Emerging Acute Respiratory Infections confirmed a high prevalence of dementia in elderly people hospitalized. Dementia is likely to be associated with a variety of comorbidities, in particular, frailty, which can further exacerbate the risk of serious infection. In addition, up to a third of patients with COVID-19 have demonstrated cerebral/neurological sequelae with direct (brain infection, vascular effects) and indirect (host immune response, treatment impact) effects. It is possible that the infection may accentuate any pre-existing neurodegenerative disease. Several studies have described cognitive decline, depressed mood, anxiety, insomnia, and post-traumatic stress disorder in a proportion of patients after discharge. Therefore, chronic illnesses, such as dementia, can be associated with higher hospitalization and mortality rates, and may exacerbate the vulnerability of elderly people and the breakdown of their caregivers.